1986
DOI: 10.1093/bja/58.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and Halothane for Outpatient Dental Anaesthesia in Children

Abstract: A trial was undertaken in children to compare the use of halothane and isoflurane in outpatient dental anaesthesia. A wholly inhalation technique was chosen and nitrous oxide in oxygen was delivered from a Boyle's machine via a coaxial (Bain) breathing system and was supplemented with either halothane or isoflurane. Isoflurane produced significantly fewer arrhythmias than halothane but the induction of anaesthesia took longer and proved more difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…I __. 2.2 min, was less than that reported after halothane or isoflurane in one study (8.1 min), 16 it was similar to that reported after the same anaesthetics in another. ~4 Moreover, the time to full recovery after desflurane anaesthesia in this study is no different from that reported previously with halothane and isoflurane.14 The differences between the recovery from desflurane in the present study and that from halothane and isoflurane in previous studies may be attributed to (I) a 2-20-fold longer duration of anaesthesia in the present study than in previous studies, 14'16'z3 (2) greater anaesthetic concentration throughout surgery in this study (the anaesthetic concentration was maintained at ~1 MAC with 70% NzO until the completion of surgery), (3) differences in the definition of full recovery, and (4) the use of intramuscular codeine for postoperative analgesia.…”
Section: Discussionsupporting
confidence: 61%
“…I __. 2.2 min, was less than that reported after halothane or isoflurane in one study (8.1 min), 16 it was similar to that reported after the same anaesthetics in another. ~4 Moreover, the time to full recovery after desflurane anaesthesia in this study is no different from that reported previously with halothane and isoflurane.14 The differences between the recovery from desflurane in the present study and that from halothane and isoflurane in previous studies may be attributed to (I) a 2-20-fold longer duration of anaesthesia in the present study than in previous studies, 14'16'z3 (2) greater anaesthetic concentration throughout surgery in this study (the anaesthetic concentration was maintained at ~1 MAC with 70% NzO until the completion of surgery), (3) differences in the definition of full recovery, and (4) the use of intramuscular codeine for postoperative analgesia.…”
Section: Discussionsupporting
confidence: 61%
“…experiences with isoflurane showed that the theoretical advantages of its use were often negated Table 2 shows that patients in Group H took significantly longer to lose their lash reflex (P=0.028) by problems with airway irritation and poor patient acceptance (6)(7)(8)12). However, not all of the early and to tolerate the presence of the face mask (P= 0.0072).…”
Section: Resultsmentioning
confidence: 99%
“…The complications has been found to be less when using introduction of isoflurane with its lower blood this technique, although it is still similar to that solubility offered a new agent with a potentially experienced when using halothane incrementally faster onset of anaesthetic induction (3)(4)(5). However, (6)(7)(8)(9)(10). A previous study by one of the authors it is also an irritant vapour with a powerful, pungent demonstrated that in infants, the high-concentration isoflurane technique caused fewer airway complications and hypoxaemia than an incremental no direct comparison between high equipotent vapour concentrations of halothane and isoflurane rubber bag.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Inhalational induction of anaesthesia is particularly suitable for smaller children in whom venous access may be difficult. The choice of isoflurane avoids such drawbacks as the onset of dysrhythmias (Cattermole et al 1986), myocardial depression (Gallagher, Shields & Black 1986), and the very rare hazard of hepatitis (Kenna et al 1987). It has previously been reported that induction of anaesthesia with isoflurane in unpremedicated children may be prolonged and that the irritant effect on the airway may interfere with tissue oxygenation (Sampaio et al 1989).…”
Section: Discussionmentioning
confidence: 99%